Kolonizacja? Rekolonizacja? Polonizacja? czyli Rosja po polsku - Jastrzębska, Joanna (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2015)
The essay aims at showing the possible ways of interpreting the political aspects of literature. A proposed way is based on the functionalization of post-colonial criticism tools for the purpose of contemporary literary studies. The author discusses concept of post-colonial research in connection with Polish literature about Russia and Russians and draws attention to the works of Polish reporters who describe Russia after 1991. The suggestion is that the authors of Polish narratives try to symbolically colonize Russian reality in a political way.